Success and University for Indigenous students: A review of Higher Education in Australia - Garcia Garcia, Edisson Giovanny; Rolls, Nicola; Guenther, John; Woodroffe, Tracy (The International Indigenous Policy Journal, 2025)
This paper examines how well Higher Education (HE) meets the aspirations of Indigenous people in Australia, especially as reflected in the public policy discourse and its measurements of success. Through a literature review, the paper analyses current public policy and experiences of Indigenous students to identify the extent to which the HE system meets the needs of Indigenous people, especially those from remote areas. From a critical examination of the concept of success, the current limitations within HE are presented, and recommendations are made to help ensure that Indigenous Australians' aspirations and needs for HE are more firmly at the forefront of policy, design and delivery of HE in Australia.